Tuning selectivity in macrotricyclic carbohydrate receptors; CH → N mutations in aromatic spacers - Ryan, Theo (My University, 2004)
Dipicolinoyl spacer groups are used to control the conformational and H-bonding properties of tricyclic carbohydrate receptors 3 and 4. Binding selectivities are changed in relation to all-isophthaloyl system 1b.
PUBLISHED